Working Capital Training and Preparation of Business Cash Projections for Titi Putih Village Community, Lima Puluh Pesisir District, Batubara Regency, North Sumatra - Muda, Iskandar; Maksum, Azhar; Azhar, Ibnu Austrindanney Sina; Astuti, Windi (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this paper is to provide training in the preparation of working capital for residents of Titi Putih village, Batubara Regency, North Sumatra by identifying the allocation of the Production budget, Raw Material Budget, Labor Budget and Sales Budget so that the ideal Working Capital scheme with a certain point of sale will generate cash flow. predictable entry so that people can avoid loans from moneylenders and banking institutions. The method used is a pattern of socialization, training, strengthening governance and monitoring and evaluation. The participants of the activity were residents of Titi Putih village, Batubara. The results show that with the Applied Excel application feature training related to the Preparation of Working Capital by identifying the allocation of the Production budget, Raw Material Budget, Labor Budget and Sales Budget so that the Working Capital scheme will be able to identify certain sales points that will generate cash inflows.